The business of slavery and the rise of American capitalism, 1815-1860 - Schermerhorn, Calvin, 1975- (Yale University Press, 2015)
"Focuses on networks of people, information, conveyances, and other resources and technologies that moved slave-based products from suppliers to buyers and users." (page 3) The book examines the credit and financial systems that grew up around trade in slaves and products made by slaves.
Keywords: Slave trade -- United States -- History -- 19th century.; Slave traders -- United States -- History -- 19th century.; Enslaved persons -- United States -- Social conditions -- 19th century.; Slavery -- Economic aspects -- United States.; Capitalism -- United States -- History -- 19th century.; Traite des esclaves -- États-Unis -- Histoire -- 19e siècle.; Marchands d'esclaves -- États-Unis -- Histoire -- 19e siècle.; Esclaves -- États-Unis -- Conditions sociales -- 19e siècle.; BUSINESS & ECONOMICS -- Labor.; POLITICAL SCIENCE -- Labor & Industrial Relations.; HISTORY -- United States -- 19th Century.; Capitalism; Slave trade; Slave traders; Slavery -- Economic aspects; Enslaved persons -- Social conditions; United States; Sklaverei; Kapitalismus; USA; Slavhandel -- historia.; Slavhandel -- sociala aspekter.; Slavhandel -- ekonomiska aspekter.; Sklaverei.; Kapitalismus.; Wirtschaftsgeschichte.; USA.; 1800-1899; Electronic books.; History